Silent films: a source of contestation between the Victorian & Progressive Eras of America - Muhammad Sulhan Bin Sulaiman (Nanyang Technological University, 2023)
Scholars have argued that silent films were a political tool during Progressive American history. Films are argued to be political based on their narrative and how they were used to support certain agendas of various groups. This paper seeks to understand how these films could be made to be such malleable political tools. The same scholars who argue for a films’ political element goes further by developing their own lenses as to how to categorise a film as progressive. Using such lenses, the scholars agree that films of the Progressive Era, strove to push out beliefs belonging to the Victorian era. However, through the same lenses, films and their messages themselves are not analysed deeply to understand the nature of such films before arguing said statement. The films of two renowned progressive filmmakers, David Wark Griffith and Lois Weber, are analysed to understand the contestation of values apparent in said films that derive from different eras of American history. Through their films, it will be shown that films of that time contained contradictory ideas that belonged to both eras. This paper serves as a reminder for those attempting to study American silent film that such a basic acknowledgement of this fact needs to be done before analysis of such films are made, to truly discuss the impact of such films in American society, as every film during the era has its strengths and limitations regarding whatever purpose such films were used for.